2012
DOI: 10.1270/jsbbs.61.566
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of soybean germplasm conserved in NIAS genebank and development of mini core collections

Abstract: Genetic variation and population structure among 1603 soybean accessions, consisted of 832 Japanese landraces, 109 old and 57 recent Japanese varieties, 341 landrace from 16 Asian countries and 264 wild soybean accessions, were characterized using 191 SNP markers. Although gene diversity of Japanese soybean germplasm was slight lower than that of exotic soybean germplasm, population differentiation and clustering analyses indicated clear genetic differentiation among Japanese cultivated soybeans, exotic cultiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
113
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 113 publications
(118 citation statements)
references
References 59 publications
5
113
0
Order By: Relevance
“…To assess the distribution of the shattering-resistance gene pdh1, we surveyed soybean germplasm in a mini-core collection established by Kaga et al (31). This collection currently consists of 79 Japanese and 80 non-Japanese accessions, mostly landraces, and maximizes genetic diversity with its small population size (31). Sequencing of the Pdh1 coding region of the 159 active accessions in this collection revealed no other genotypes besides those of Hayahikari, Toyomusume, and Misuzudaizu, with the exception of a heterozygous genotype between Hayahikari and Toyomusume that is most likely the product of outcrossing (Table S1).…”
Section: Resultsmentioning
confidence: 99%
“…To assess the distribution of the shattering-resistance gene pdh1, we surveyed soybean germplasm in a mini-core collection established by Kaga et al (31). This collection currently consists of 79 Japanese and 80 non-Japanese accessions, mostly landraces, and maximizes genetic diversity with its small population size (31). Sequencing of the Pdh1 coding region of the 159 active accessions in this collection revealed no other genotypes besides those of Hayahikari, Toyomusume, and Misuzudaizu, with the exception of a heterozygous genotype between Hayahikari and Toyomusume that is most likely the product of outcrossing (Table S1).…”
Section: Resultsmentioning
confidence: 99%
“…Hypoxia tolerance was moderate in the Chinese accessions, with a narrow range, based on the PC2 score. Genetic diversity of Chinese and Taiwanese accessions is reported to be wide (Kaga et al, 2012) because Chinese accessions are grown in a wide range of environments. However, we did not find extremely high hypoxia tolerance in root at the seedling stage in the 22 Chinese and Taiwanese accessions we tested (Figure 3(a)).…”
Section: Correlation Between the Results In Experiments 1 (Hydroponicsmentioning
confidence: 99%
“…Since its domestication, it has spread widely and is grown around the world. Kaga et al (2012) showed phenotypic variation in parameters such as seed size and flowering time among accessions distributed around the world. Although waterlogging tolerance during vegetative growth has not been compared among Asian accessions (including Chinese accessions) and those in the United States, their tolerance during reproductive growth is higher than that of American accessions (VanToai et al, 1994(VanToai et al, , 2010.…”
Section: Experiments 1: Evaluation Of Hypoxia Tolerance Of Soybean In mentioning
confidence: 99%
See 1 more Smart Citation
“…To this end, all types of data can be used, e.g., of genealogy, morphologic traits, the biochemical profile, genotypic data, and many others. Commonly, SSR markers are used in genetic studies, due to their multiallelic nature and repeatability in laboratories (Kaga et al 2012, Rodrigues et al 2008. The characterization of plant genotypes by PCR-based DNA markers provides reliable data, for being free of the influence of environmental factors, unlike other methods.…”
Section: Introductionmentioning
confidence: 99%